Digital bioethics... Next step forward? - Giuseppe Corasaniti (European Journal of Privacy Law & Technologies)
The integration of artificial intelligence (AI) in healthcare raises ethical and legal challenges, requiring a strong regulatory framework. The WHO emphasises autonomy, transparency and accountability in the use of AI, while the EU regulation classifies medical AI as high-risk, imposing compliance and data protection obligations. Liability remains a key issue due to AI's opaque decision-making processes. Digital bioethics highlights the need for interdisciplinary collaboration to ensure equitable access, mitigate bias, and balance technological advances with patient rights and legal responsibilities. A holistic approach is essential for the ethical integration of AI in medicine.